Temporal variation of physico-chemical, microbiological, and parasitological properties of poultry manure from two egg production systems - Rizzo, Pedro Federico; Bres, Patricia Alina; Young, Brian Jonathan; Zubillaga, Marta Susana; Riera, Nicolas; Beily, María Eugenia; Argüello, Andrea; Crespo, Diana Elvira; Sánchez, Antoni; Komilis, Dimitrios (Springer, 2020)
Egg production has increased worldwide and, consequently, there is a large volume of poultry manure generated. The principal egg production systems are the caged ones, namely the conventional and the automated. The aim of this study was to evaluate the temporal variability of the physico-chemical, microbiological, and parasitological properties of poultry manure from both systems. Three conventional and four automated farms were studied. The main variables analyzed differed significantly between systems. Poultry manure from conventional system had the highest values of pH, total solids, C:N, phosphorous, sulfate, selected cations, and some microorganisms and parasites. Poultry manure from automated system had the highest values of electrical conductivity, volatile solids, nitrogen content, and soluble fraction of Ca, Mg, and Mn, among others. The lowest temporal variability of the measured parameters was observed in the automated system. Overall, all measured parameters, except nitrogen, had their highest values in the warmest season. The presence of pathogen microorganisms and parasites and the Na and Zn concentrations indicate that a special management before soil application should be considered. This study could contribute to the development of management strategies for poultry manure in each system, such as control of ambient conditions within the facilities and waste treatment.